Kewirausahaan kuliner pisang coklat sebagai penunjang finansial mahasiswa di Kota Malang - Febrian, Guntur Cahyo; Pradana, Frengky; Alanhar, Yuridul Izzata Arafat; Kuncoro, Bagas Dwi (Maliki Interdisciplinary Journal, 2023)
Students are students who have entered the working period, but are still not able to work freely because they have responsibility as a student. As a student, of course you have many needs that still need to be met, which are sometimes still inadequate. The solution to this problem is entrepreneurship, one business that is easy to do is a culinary business. It doesn’t take time, cheap capital, and is easy to build are the advantages of this business. One of the culinary choices that is now popular, familiar and familiar on people’s tongues is chocolate banana. With the composition and tenacity of entrepreneurs, this business will be a promising business and be able to solve the problems of students in the financial sector.